Method for improving crystallization capacity of semi-aromatic nylon and modified semi-aromatic nylon
By mixing semi-aromatic nylon with an alkaline solution after heat treatment, the problem of adding additives in the prior art to improve the crystallinity of semi-aromatic nylon is solved, and the crystallization capacity under the conditions without additives is improved, and the crystallization performance of the material is significantly improved.
Patent Information
- Application Number
- CN202411963258.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, improving the crystallinity of semi-aromatic nylons usually requires the addition of additives, resulting in process complexity and increased costs, and lack of effective methods under conditions without additives.
Modified semi-aromatic nylon is prepared by mixing semi-aromatic nylon with an alkaline solution and after heat treatment, its crystallization ability is improved. The mass ratio of the alkali in the alkali solution to the mass of semi-aromatic nylon is ≥0.005:1. The alkali includes hypophosphite, phosphite, phosphate or alkali metal salt, and the heat treatment temperature is greater than 60°C.
Without the need to add nucleating agents or additives, the crystallization capacity of semi-aromatic nylon is effectively improved, its crystallization temperature is improved, and the cold crystallization enthalpy is reduced, significantly improving the crystallization performance of the material.
Smart Images

Figure BDA0005217706110000033 
Figure BDA0005217706110000034 
Figure BDA0005217706110000161
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the crystallization ability of semi-aromatic nylon and modified semi-aromatic nylon. Background Art
[0002] Semi-aromatic nylon is a kind of polymer material with excellent comprehensive performance. Its main chain contains both aromatic rings and fatty chains, so it has both the excellent performance of aromatic nylon and the good molding and processing properties of aliphatic nylon. This kind of material generally has the advantages of high temperature resistance, corrosion resistance and low water absorption. In recent years, it has been widely used in the fields of electronics, automobile industry, equipment manufacturing, etc. Among them, poly(m-phenylenediamine adipamide) (MXD6) performs particularly well. It is a semi-crystalline polyamide resin formed by the condensation polymerization of adipic acid and m-phenylenediamine. It has excellent thermal stability, gas barrier properties, corrosion resistance, mechanical properties, processing properties and low water absorption. It is particularly suitable for flexible packaging films, barrier bottles, automotive parts, electronics, etc.
[0003] MXD6's high strength, high rigidity, high heat deformation temperature, easy molding and manufacturing performance enable it to be used in engineering plastics fields such as automotive parts and electronic and electrical plug-ins. However, if the material's crystallization ability is weak, the molding cycle will be prolonged and production efficiency will be reduced. In order to meet processing requirements, its crystallization ability needs to be improved.
[0004] MXD6 is often used in multi-layer composite packaging materials due to its excellent barrier properties, mainly used as a film. Barrier properties in a broad sense refer to the ability to significantly prevent the passage of gas (such as steam) or liquid molecules. Generally speaking, the crystal region of a polymer has a regular arrangement of molecular chains and a tight and orderly accumulation of molecules, which increases the density and can effectively block the penetration of small molecules. Therefore, improving the crystallinity of the polymer also has an important influence on the improvement of barrier properties.
[0005] At present, the existing technology for improving the crystallinity of MXD6 is generally achieved through complex methods such as adding additives for modification. Although the crystallinity can be improved, it not only makes the operation process complicated, but also increases the cost.
[0006] Therefore, how to provide a method for improving the crystallinity of semi-aromatic nylon without adding an auxiliary agent is a technical problem to be solved urgently in the art. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the problem that the method for improving the crystallinity of semi-aromatic nylon in the prior art needs to be achieved through complex methods such as agent modification, and provide a method for improving the crystallization ability of semi-aromatic nylon and modified semi-aromatic nylon.
[0008] The present invention provides a method for improving the crystallization ability of semi-aromatic nylons such as MXD6 and MXD10, and a modified semi-aromatic nylon. The method for improving the crystallization ability of semi-aromatic nylon in the present invention is to improve the crystallization ability of semi-aromatic nylon (such as semi-aromatic nylon chips) by post-treatment with an alkaline solution, and the semi-aromatic nylon chips are prepared by solution polymerization.
[0009] The method of the present invention can effectively solve the following problems:
[0010] The crystallization ability of semi-aromatic nylon can be improved without adding nucleating agents, additives and other modifications, for example, the crystallization ability of chip particles can be improved when the polymerization process conditions and the polymer molecular weight are determined.
[0011] The present invention provides a method for improving the crystallization ability of semi-aromatic nylon, which comprises the following steps:
[0012] The modified semi-aromatic nylon is prepared by mixing the semi-aromatic nylon with an alkaline solution and subjecting the mixture to heat treatment;
[0013] The mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is ≥ 0.005:1;
[0014] The alkali in the alkaline solution includes hypophosphite, phosphite, phosphate or alkali metal salt;
[0015] The temperature of the heat treatment is greater than 60°C.
[0016] In the present invention, the shape of the semi-aromatic nylon is not limited, and any conventional shape in the art is applicable to the present invention. When the contact area between the semi-aromatic nylon and the alkaline solution is larger, the amount of alkaline solution used is less, which is more conducive to cost saving.
[0017] In some embodiments of the present invention, the semi-aromatic nylon is in a granular form. The particle size of the semi-aromatic nylon particles may be a conventional particle size in the art.
[0018] In some embodiments of the present invention, the semi-aromatic nylon is in strip shape.
[0019] In the present invention, the semi-aromatic nylon may be a conventional polyamide in the art whose main chain contains both aromatic rings and fatty chains. Polyamide refers to a polymer containing -NHCO- repeating structural units on the main chain of the molecule.
[0020] In some embodiments of the present invention, the structural formula of the semi-aromatic nylon is as follows:
[0021] Where a and n are positive integers, and Y is C 6 -C 8 of phenyl.
[0022] In some embodiments of the present invention, a is a positive integer of 2-11, such as 4 or 8.
[0023] In some embodiments of the present invention, Y is
[0024] In some embodiments of the present invention, the structural formula of the semi-aromatic nylon is as follows:
[0025]
[0026] In some embodiments of the present invention, the relative viscosity of the semi-aromatic nylon is 2.0-3.0, such as 2.24 or 2.61.
[0027] In the present invention, the relative viscosity test method is: dissolving the sample in concentrated sulfuric acid with a concentration of 0.01 g / mL, using a Wushi viscometer at a temperature of 25°C to measure the outflow time t0 and t1 of the concentrated sulfuric acid solvent and the polymer solution respectively, and calculating according to the relative viscosity formula: relative viscosity = t1 / t0.
[0028] In some embodiments of the present invention, the number average molecular weight of the semi-aromatic nylon is 10,000-500,000, such as 32,701 or 21,094.
[0029] In some embodiments of the present invention, the weight average molecular weight of the semi-aromatic nylon is 10,000-500,000, such as 74,259 or 48,968.
[0030] In the present invention, the semi-aromatic nylon can be prepared by solution polymerization conventionally in the art.
[0031] In some embodiments of the present invention, the method for preparing the semi-aromatic nylon comprises the following steps:
[0032] In the presence of a catalyst, a dibasic acid, a diamine and a solvent are mixed to form a solution, and a polymerization reaction is carried out to obtain the semi-aromatic nylon.
[0033] In some embodiments of the present invention, the catalyst is selected from at least one of phosphoric acid, hypophosphorous acid, phosphorous acid, phosphates, hypophosphites, phosphites, phosphites, and phosphates.
[0034] In some embodiments of the present invention, the amount of the catalyst added is 0.01-0.2 wt %, for example 0.03 wt %, based on the total weight of the dibasic acid, the diamine and the catalyst.
[0035] In some embodiments of the present invention, the diamine is selected from one or more of p-phenylenediamine, m-phenylenediamine, p-phenylenediamine and m-phenylenediamine, preferably m-phenylenediamine.
[0036] In some embodiments of the present invention, the dibasic acid is selected from aliphatic dibasic acids having 4-13 carbon atoms, such as aliphatic dibasic acids having 6 or 10 carbon atoms.
[0037] In some embodiments of the present invention, the dibasic acid includes but is not limited to: succinic acid, adipic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, preferably adipic acid and sebacic acid.
[0038] In some embodiments of the present invention, the molar ratio of the dibasic acid to the diamine is (0.96-1.05):1, preferably (0.98-1.03):1, for example 1.02:1.
[0039] In some embodiments of the present invention, the solvent is desalted water.
[0040] In the present invention, the desalted water refers to the product obtained by removing chemical salts (cations and anions) from water through a series of process flows. This process is called desalination, and the main methods include electrodialysis and reverse osmosis.
[0041] In some embodiments of the present invention, the concentration of the solute in the solution is 50-80wt%, preferably 55-75wt%. The solute refers to the catalyst, the dibasic acid, and the diamine.
[0042] In the present invention, the temperature of the polymerization reaction can be selected according to the dibasic acid and diamine used.
[0043] In some embodiments of the present invention, the dibasic acid is adipic acid, the diamine is meta-xylylenediamine, and the polymerization reaction temperature is 240-290°C, for example, 268°C.
[0044] In some embodiments of the present invention, the dibasic acid is sebacic acid, the diamine is meta-xylylenediamine, and the polymerization reaction temperature is 210-260°C, for example, 220°C.
[0045] In some embodiments of the present invention, the polymerization reaction process includes a positive pressure reaction process, a normal pressure reaction process, and a negative pressure reaction process in sequence. The positive pressure condition refers to a pressure higher than the normal pressure condition, that is, a condition higher than one atmosphere. The negative pressure condition refers to a pressure lower than the normal pressure condition, that is, a condition lower than one atmosphere.
[0046] During the positive pressure reaction, the by-products produced are discharged through exhaust gas, and the pressure can be maintained at 400-800 kPa, such as 600 kPa.
[0047] During the positive pressure reaction, the maintaining time may be 0.5-2 h, for example 1.5 h.
[0048] During the normal pressure reaction, the holding time may be 20-60 min, for example 25 min.
[0049] During the negative pressure reaction, the vacuum degree may be -100 to -20 kPa, for example -80 kPa.
[0050] During the negative pressure reaction, the reaction time may be 10-100 min, such as 30 min or 60 min.
[0051] In some embodiments of the present invention, the method for preparing the semi-aromatic nylon comprises the following steps:
[0052] In the presence of a catalyst, diacid, diamine and solvent are added to a reactor, stirring is started, and the temperature is raised to carry out a polymerization reaction. During the reaction, the by-products produced are discharged through exhaust, and the pressure in the reactor is adjusted to promote the polycondensation reaction. After the polymerization is completed, the material is squeezed out from the discharge port by pressurization, and after water cooling, it can be sliced through a pelletizer.
[0053] In the present invention, the crystallization ability of semi-aromatic nylon can be improved by treating it with an alkaline solution.
[0054] In some embodiments of the present invention, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is (0.005-0.1):1, for example (0.005-0.05):1, and also for example (0.005-0.03):1.
[0055] In some embodiments of the present invention, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is 0.005:1, 0.03:1 or 0.1:1.
[0056] In some embodiments of the present invention, the alkali in the alkaline solution may be the same type as the catalyst salt used in the semi-aromatic nylon polymerization process, such as an alkali metal hypophosphite.
[0057] In the present invention, alkali metals refer to the six metal elements in Group IA of the periodic table except hydrogen (H), including lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr).
[0058] In the present invention, alkaline earth metals refer to the six metal elements of Group IIA in the periodic table, including beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba) and radium (Ra).
[0059] In some embodiments of the present invention, the hypophosphite includes an alkali metal hypophosphite or an alkaline earth metal hypophosphite. The alkali metal hypophosphite may be potassium hypophosphite and / or sodium hypophosphite. The alkaline earth metal hypophosphite may be magnesium hypophosphite.
[0060] In some embodiments of the present invention, the phosphite includes an alkali metal phosphite or an alkaline earth metal phosphite. The alkali metal phosphite may be potassium phosphite and / or sodium phosphite. The alkaline earth metal phosphite may be calcium phosphite.
[0061] In some embodiments of the present invention, the phosphate includes an alkali metal phosphate or an alkaline earth metal phosphate. The alkali metal phosphate may be potassium phosphate and / or sodium phosphate. The alkaline earth metal phosphate may be calcium phosphate and / or magnesium phosphate.
[0062] In some embodiments of the present invention, the alkali metal salt is a sodium salt and / or a potassium salt, such as potassium hypophosphite, sodium hypophosphite, potassium phosphite, sodium phosphite, potassium phosphate, sodium phosphate, C 1 ~C 5 Sodium salt of fatty acids, C 1 ~C 5 Potassium salts of fatty acids.
[0063] Among them, the C 1 -C 5 The fatty acids can be C 1 -C 4 Fatty acids, such as formic acid, acetic acid, propionic acid, and butyric acid.
[0064] Among them, the C 1 ~C 5 The fatty acid sodium salt may be one or more of sodium formate, sodium acetate, sodium propionate and sodium butyrate, such as sodium acetate.
[0065] Among them, the C 1 ~C 5 The fatty acid potassium salt may be one or more of potassium formate, potassium acetate, potassium propionate and potassium butyrate.
[0066] In some embodiments of the present invention, the alkali in the alkaline solution can be selected from one or more of hypophosphites, phosphites, phosphates and alkali metal salts.
[0067] In some embodiments of the present invention, the alkali in the alkaline solution can be selected from one or more of the following combinations: potassium hypophosphite, sodium hypophosphite, magnesium hypophosphite, potassium phosphite, sodium phosphite, calcium phosphite, potassium phosphate, sodium phosphate, calcium phosphate, magnesium phosphate, sodium formate, potassium formate, sodium acetate, potassium acetate, sodium propionate, potassium propionate, sodium butyrate and potassium butyrate.
[0068] In some embodiments of the present invention, the alkali in the alkaline solution is selected from one or more of sodium hypophosphite, sodium acetate, potassium phosphite, magnesium phosphate and sodium formate, such as sodium hypophosphite, sodium acetate, potassium phosphite, magnesium phosphate or sodium formate.
[0069] In some embodiments of the present invention, the temperature of the heat treatment is 80-150°C, preferably 90-150°C, for example 100-150°C, for example 80°C, 100°C, 120°C or 150°C.
[0070] In some embodiments of the present invention, the heat treatment time is 1 to 100 hours, such as 2 to 90 hours, and for example 2 hours, 24 hours, 60 hours or 90 hours.
[0071] In the present invention, the heat treatment process can be carried out under normal pressure or positive pressure. The positive pressure condition refers to a pressure higher than normal pressure, that is, a pressure higher than one atmosphere.
[0072] In some embodiments of the present invention, the heat treatment process is carried out under normal pressure. When the heat treatment process is carried out under normal pressure, the heat treatment time may be 24 to 90 hours, such as 24 hours, 60 hours or 90 hours.
[0073] In some embodiments of the present invention, the heat treatment process is carried out under positive pressure. When the heat treatment is carried out under positive pressure, the heat treatment time can be shorter than that under normal pressure. When the heat treatment process is carried out under positive pressure, the heat treatment time can be 1 to 24 hours, for example, 2 to 6 hours.
[0074] The positive pressure condition can be formed by heating in a closed environment.
[0075] In some embodiments of the present invention, the ratio of the mass g of the semi-aromatic nylon to the volume mL of the alkaline solution is 1:1 to 1:10 g / mL, for example 1:2 g / mL.
[0076] In some embodiments of the present invention, the solvent in the alkaline solution is water.
[0077] In some embodiments of the present invention, the mass concentration of the alkali in the alkaline solution is 0.1-10 wt %, such as 0.5-5 wt %, such as 3 wt %.
[0078] In the present invention, the volume of the alkaline solution can be selected according to whether the semi-aromatic nylon can be fully immersed in the solution. Generally speaking, the same volume of alkaline solution can process more particles and further save process costs.
[0079] In one embodiment of the present invention, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is (0.005-0.05):1, the alkali in the alkaline solution includes hypophosphite, phosphite, phosphate or alkali metal salt, and the temperature of the heat treatment is 80-150°C.
[0080] In one embodiment of the present invention, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is (0.005-0.05):1, the alkali in the alkaline solution is sodium hypophosphite, and the temperature of the heat treatment is 80-150°C, preferably 100-150°C.
[0081] In one embodiment of the present invention, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is 0.03:1, the alkali in the alkaline solution is sodium acetate, potassium phosphite, magnesium phosphate or sodium formate, and the heat treatment temperature is 100°C.
[0082] In some embodiments of the present invention, the method for improving the crystallization ability of semi-aromatic nylon comprises the following steps:
[0083] Add 50 g of semi-aromatic nylon and 100 mL of alkaline solution of corresponding concentration into a container, stir, heat to a specified temperature, keep the temperature constant for a specified time, and dry the material after it is cooled to obtain semi-aromatic nylon with improved crystallization ability.
[0084] In some embodiments of the present invention, the crystallization temperature of the modified semi-aromatic nylon is higher than the crystallization temperature of the semi-aromatic nylon.
[0085] In the present invention, the crystallization temperature generally refers to the temperature required for a substance to transform from a molten state to a crystal.
[0086] In some embodiments of the present invention, the difference in crystallization temperature between the modified semi-aromatic nylon and the semi-aromatic nylon is ≥0.3°C, for example, 0.4-4.5°C, and also for example, 0.49°C, 0.76°C, 1.33°C, 1.35°C, 1.69°C, 1.87°C, 1.92°C, 1.95°C, 2.63°C, 2.81°C, 2.92°C, 3.98°C or 4.03°C.
[0087] In some embodiments of the present invention, the cold crystallization enthalpy of the modified semi-aromatic nylon is lower than the cold crystallization enthalpy of the semi-aromatic nylon.
[0088] In some embodiments of the present invention, the difference between the cold crystallization enthalpy ΔHc (J / g) of the modified semi-aromatic nylon and the semi-aromatic nylon is ≤-2.0 J / g, for example, -2.0 to -15.0 J / g, and for example, -2.03 J / g, -2.85 J / g, -2.86 J / g, -4.02 J / g, -4.32 J / g, -4.67 J / g, -5.06 J / g, -5.27 J / g, -6.38 J / g, -6.7 J / g, -7.16 J / g, -8.5 J / g, -9.18 J / g, -10.4 J / g or -11.29 J / g.
[0089] In some embodiments of the present invention, the semi-aromatic nylon is poly(meta-xylylene adipamide), the crystallization temperature of the poly(meta-xylylene adipamide) is greater than 159.22° C., and the cold crystallization enthalpy ΔHc (J / g) of the poly(meta-xylylene adipamide) is less than 19.59 J / g.
[0090] Wherein, the crystallization temperature of the poly(m-xylylene adipamide) may be 159.4-163.5°C, for example, 159.47°C, 159.74°C, 160.31°C, 160.33°C, 160.67°C, 160.85°C, 160.9°C, 160.93°C, 161.61°C, 161.79°C, 161.9°C, 162.96°C or 163.01°C.
[0091] Wherein, the cold crystallization enthalpy ΔHc of the poly(m-xylylene adipamide) may be 8.0 to 19.0 J / g, for example, 8.9 J / g, 9.79 J / g, 11.01 J / g, 11.69 J / g, 13.03 J / g, 13.49 J / g, 13.81 J / g, 14.92 J / g, 15.13 J / g, 15.52 J / g, 15.87 J / g, 16.17 J / g, 17.33 J / g or 18.16 J / g.
[0092] In some embodiments of the present invention, the semi-aromatic nylon is poly(meta-xylylene sebacate), and the cold crystallization enthalpy ΔHc (J / g) of the poly(meta-xylylene sebacate) is less than 12.74 J / g, for example, 9.89 J / g.
[0093] The present invention also provides a method for improving the crystallization ability of semi-aromatic nylon, which comprises the following steps:
[0094] The modified semi-aromatic nylon is prepared by mixing the semi-aromatic nylon with an alkaline solution and subjecting the mixture to heat treatment;
[0095] The crystallization temperature of the modified semi-aromatic nylon is higher than the crystallization temperature of the semi-aromatic nylon, and the difference in crystallization temperature between the modified semi-aromatic nylon and the semi-aromatic nylon is ≥0.3°C; and / or the cold crystallization enthalpy of the modified semi-aromatic nylon is lower than the cold crystallization enthalpy of the semi-aromatic nylon, and the difference in cold crystallization enthalpy ΔHc (J / g) between the modified semi-aromatic nylon and the semi-aromatic nylon is ≤-2.0J / g.
[0096] In some embodiments of the present invention, compared with the semi-aromatic nylon, the modified semi-aromatic nylon is more likely to produce a crystallization peak during the cooling crystallization process. That is, the crystallization peak of the modified semi-aromatic nylon is more obvious in the spectrum (such as DSC spectrum).
[0097] Wherein, the semi-aromatic nylon can be as described above.
[0098] Wherein, the alkaline solution can be as described above.
[0099] Wherein, the alkali in the alkaline solution can be as described above.
[0100] Wherein, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon can be as described above.
[0101] Wherein, the heat treatment process can be as described above.
[0102] Wherein, the crystallization temperature of the modified semi-aromatic nylon may be as described above.
[0103] Wherein, the cold crystallization enthalpy of the modified semi-aromatic nylon may be as described above.
[0104] The present invention provides a method for preparing modified semi-aromatic nylon, which comprises the following steps:
[0105] The modified semi-aromatic nylon is prepared by mixing the semi-aromatic nylon with an alkaline solution and subjecting the mixture to heat treatment;
[0106] The mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is ≥ 0.005:1;
[0107] The alkali in the alkaline solution includes hypophosphite, phosphite, phosphate or alkali metal salt;
[0108] The temperature of the heat treatment is greater than 60°C.
[0109] Wherein, the semi-aromatic nylon can be as described above.
[0110] Wherein, the alkaline solution can be as described above.
[0111] Wherein, the alkali in the alkaline solution can be as described above.
[0112] Wherein, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon can be as described above.
[0113] Wherein, the heat treatment process can be as described above.
[0114] Wherein, the crystallization temperature of the modified semi-aromatic nylon may be as described above.
[0115] Wherein, the cold crystallization enthalpy of the modified semi-aromatic nylon may be as described above.
[0116] The invention also provides a modified semi-aromatic nylon, which is prepared by the method.
[0117] The present invention also provides poly(meta-xylylene adipamide), wherein the crystallization temperature of the poly(meta-xylylene adipamide) is greater than 159.22° C., and the cold crystallization enthalpy ΔHc (J / g) of the poly(meta-xylylene adipamide) is less than 19.59 J / g.
[0118] The present invention also provides poly(meta-xylylene sebacate), wherein the cold crystallization enthalpy ΔHc (J / g) of the poly(meta-xylylene sebacate) is less than 12.74 J / g, for example, 9.89 J / g.
[0119] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0120] The reagents and raw materials used in the present invention are commercially available.
[0121] The positive and progressive effects of the present invention are:
[0122] In the present invention, the crystallization ability of semi-aromatic nylon is improved by post-treatment with an alkaline solution, wherein the crystallization temperature of semi-aromatic nylon (such as MXD6 and MXD10) is increased, and the crystallization peak is more obvious; or, although the crystallization peak is not obvious, the cold crystallization enthalpy is significantly reduced, for example, the cold crystallization enthalpy of MXD6 can be reduced from 20 to 8-9. DETAILED DESCRIPTION
[0123] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0124] In the following embodiments and comparative examples:
[0125] Molecular weight and molecular weight distribution: tested by gel permeation chromatography (GPC), the solvent is hexafluoroisopropanol;
[0126] Relative viscosity: Dissolve the dried sample in concentrated sulfuric acid at a concentration of 0.01 g / mL. Use a Wushi viscometer at 25°C to measure the outflow time t0 and t1 of the concentrated sulfuric acid solvent and the polymer solution, respectively. Calculate the relative viscosity according to the relative viscosity formula: relative viscosity = t1 / t0.
[0127] Normal pressure conditions refer to one atmosphere, and one standard atmosphere is 101325Pa.
[0128] Desalinated water is the product of removing chemical salts (cations and anions) from water through a series of process flows. This process is called desalination, and the main methods include electrodialysis and reverse osmosis.
[0129] Preparation Example 1 Preparation of polyamide MXD6
[0130] Solution polymerization stage: slowly add weighed 2658g of adipic acid, 1.9g of sodium hypophosphite, 2770g of desalted water, and 2428g of m-xylylenediamine into a pressure autoclave; the molar ratio of adipic acid to m-xylylenediamine is 1.02:1; vacuumize and fill with nitrogen, and repeat vacuumizing and filling with nitrogen 3 times.
[0131] The temperature was raised to 268°C under stirring. When the pressure in the reactor reached 600 kPa, the by-products were discharged by exhaust. The time was 1.5 hours. The pressure was adjusted to normal pressure and maintained for 25 minutes. The reactor was evacuated to a pressure of -80 kPa and the reaction time was 60 minutes. After the polymerization was completed, the material was squeezed out from the discharge port by filling the reactor with nitrogen. After water cooling, it was passed through a pelletizer to obtain slices.
[0132] The relative viscosity of the polyamide MXD6 chip particles is 2.61, the number average molecular weight is 32701, and the weight average molecular weight is 74259.
[0133] Preparation Example 2 Preparation of polyamide MXD10
[0134] Solution polymerization stage: slowly add weighed 3679g of sebacic acid, 1.9g of sodium hypophosphite, 2770g of desalted water, and 2428g of m-xylylenediamine into a pressure autoclave; the molar ratio of sebacic acid to m-xylylenediamine is 1.02:1; vacuumize and fill with nitrogen, and repeat vacuumizing and filling with nitrogen 3 times.
[0135] The temperature was raised to 220°C under stirring. When the pressure in the reactor reached 600 kPa, the by-products were discharged through exhaust. The time was 1.5 h. The pressure was adjusted to normal pressure and maintained for 25 min. The reactor was vacuumed to a pressure of -80 kPa. The reaction time is 30 minutes. After the polymerization is completed, The material is squeezed out from the outlet by nitrogen filling, and then it is cooled by water and passed through a pelletizer to obtain slices.
[0136] The relative viscosity of the polyamide MXD10 chip particles is 2.24, the number average molecular weight is 21094, and the weight average molecular weight is 48968.
[0137] Example 1
[0138] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0139] Example 2
[0140] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 90 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0141] Example 3
[0142] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C in a closed environment, keep the temperature constant for 2 hours, then cool down, and dry the material after it has cooled to obtain sliced particles with adjustable crystallization ability.
[0143] Example 4
[0144] 50 g of MXD6 chips obtained by polymerization in Preparation Example 1 and 3 wt % sodium acetate (sodium acetate) were added. Mass percentage is the mass percentage relative to MXD6 slice particles, MXD6 slice particles 50g, 100 mL of an aqueous solution of 1.5 g of sodium acetate (the mass percentage of sodium acetate is 3 wt%) is added to a container, the stirring is turned on, the temperature is increased, and when the material temperature reaches 100° C. in a closed environment, the temperature is kept constant for 2 hours, the temperature is lowered, and after the material is cooled, it is dried to obtain slice particles with adjustable crystallization ability.
[0145] Example 5
[0146] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 120°C in a closed environment, keep the temperature constant for 2 hours, then cool down, and dry the material after it has cooled to obtain sliced particles with adjustable crystallization ability.
[0147] Example 6
[0148] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 60 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0149] Example 7
[0150] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 150°C in a closed environment, keep the temperature constant for 2 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0151] Example 8
[0152] 50 g of MXD6 chips obtained in the polymerization in Preparation Example 1 and 3 wt % sodium hypophosphite ( The mass percentage of sodium hypophosphite is relative to the mass percentage of MXD6 sliced particles, 50g of MXD6 sliced particles, 1.5g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3wt%), 100mL of an aqueous solution is added to a container, stirring is turned on, the temperature is increased, and when the material temperature reaches 120°C in a closed environment, the temperature is kept constant for 6h, and the temperature is lowered. After the material is cooled, it is dried to obtain sliced particles with adjustable crystallization ability.
[0153] Example 9
[0154] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% potassium phosphite (the mass percentage of potassium phosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of potassium phosphite, and the mass percentage of potassium phosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0155] Example 10
[0156] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% magnesium phosphate (the mass percentage of magnesium phosphate is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of magnesium phosphate, and the mass percentage of magnesium phosphate is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0157] Embodiment 11
[0158] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium formate (the mass percentage of sodium formate is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium formate, and the mass percentage of sodium formate is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0159] Example 12
[0160] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 0.5 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 0.25 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 0.5 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0161] Embodiment 13
[0162] 50 g of MXD10 sliced particles obtained by polymerization in Preparation Example 2 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of MXD10 sliced particles, 50 g of MXD10 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) are added to a container, stirring is turned on, the temperature is increased, and when the material temperature reaches 100°C under normal pressure, the temperature is kept constant for 24 hours, the temperature is lowered, and the material is dried after cooling to obtain sliced particles with adjustable crystallization ability.
[0163] Comparative Example 1
[0164] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 30°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain the treated sliced particles.
[0165] Comparative Example 2
[0166] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 60°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain the treated sliced particles.
[0167] Comparative Example 3
[0168] 50 g of MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of desalted water were added to a container, stirring was started, and the temperature was increased. When the material temperature reached 100° C. under normal pressure, the temperature was kept constant for 24 hours, and the temperature was lowered. After the material was cooled, it was dried to obtain the treated sliced particles.
[0169] Embodiment 14
[0170] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 10 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 10 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 100°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0171] Embodiment 15
[0172] Add 50 g of the MXD6 sliced particles obtained by polymerization in Preparation Example 1 and 100 mL of an aqueous solution of 3 wt% sodium hypophosphite (the mass percentage of sodium hypophosphite is relative to the mass percentage of the MXD6 sliced particles, 50 g of MXD6 sliced particles, 1.5 g of sodium hypophosphite, and the mass percentage of sodium hypophosphite is 3 wt%) into a container, turn on stirring, increase the temperature, and when the material temperature reaches 80°C under normal pressure, keep the temperature constant for 24 hours, then cool down, and dry the material after it is cooled to obtain sliced particles with adjustable crystallization ability.
[0173] Effect Example 1
[0174] Determination of cold crystallization enthalpy and crystallization temperature: According to the test standard ISO 11357, a differential scanning calorimeter (DSC) was used for heating and cooling: in a nitrogen atmosphere, the temperature was raised to 300°C at a rate of 10°C / min, stayed for 5 minutes, then lowered to 30°C at a rate of 10°C / min, stayed for 5 minutes, and then raised to 300°C at a rate of 10°C / min. The temperature corresponding to the exothermic peak on the cooling curve is the crystallization temperature, and the exothermic peak area on the heating curve is the cold crystallization enthalpy.
[0175] The DSC crystallization performance test was performed on the sliced particles in Preparation Example 1, Preparation Example 2, Examples 1-15 and Comparative Examples 1-3. The test results are shown in Table 1 below.
[0176] Table 1
[0177]
[0178]
[0179] Due to different molecular structures, polymers have strong and weak crystallization abilities. Particles with poor crystallization ability have a weak crystallization peak when cooled, and their crystallization ability can be judged by comparing the cold crystallization enthalpy. The untreated MXD6 particles in Preparation Example 1 have a weak crystallization peak when cooled by DSC, and their crystallization ability is poor. After being treated with an alkaline solution, it is found that their crystallization temperatures are increased and their cold crystallization enthalpy is reduced, indicating that the energy required for the chain segments to start moving is reduced, and the crystallization ability of the molecular chain becomes stronger.
[0180] By comparing Examples 1-3, 5-8, 15 and Comparative Example 1-2, it can be seen that post-treatment at a temperature higher than 60°C (e.g., 80°C, 100°C, 120°C or 150°C) can improve the crystallization ability of MXD6. It can be seen from Examples 1 and 15 that under normal pressure conditions, with the increase of temperature, the increase of the crystallization temperature of the modified MXD6 and the decrease of the cold crystallization enthalpy are more obvious; it can be seen from Examples 3, 5, and 7 that under positive pressure conditions, with the increase of temperature, the increase of the crystallization temperature of the modified MXD6 and the decrease of the cold crystallization enthalpy are also more obvious.
[0181] It can be seen from Example 1 and Comparative Example 3 that alkaline solution treatment can improve the crystallization ability of MXD6. It can be seen from Examples 1, 12 and 14 that under the condition of alkali concentration ≥ 0.5wt%, alkaline solution treatment with different alkali concentrations can improve the crystallization ability of MXD6, but with the increase of alkali concentration in the alkaline solution, the crystallization ability of MXD6 will not continue to improve. As shown in Example 1 and Example 14, the degree of increase in crystallization temperature and the degree of decrease in cold crystallization enthalpy did not change significantly when the alkali concentration in the alkaline solution was increased from 3wt% to 10wt%.
[0182] It can be seen from the crystallization temperature and cold crystallization enthalpy data of the untreated MXD6 particles in Examples 1, 4, 9-11 and Preparation Example 1 that post-treatment with different alkaline solutions can improve their crystallization ability.
[0183] It can be seen from the cold crystallization enthalpy data of the untreated MXD6 particles in Example 1 and Preparation Example 1, and the cold crystallization enthalpy data of the untreated MXD10 particles in Example 13 and Preparation Example 2 that the crystallization ability of the polyamide obtained by polymerization of m-xylylenediamine and different diacids can be improved by post-treatment with an alkaline solution.
[0184] The protection content of the present invention is not limited to the following embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art should be included in the present invention and the protection scope is within the scope of the attached claims.
Claims
1. A method for improving the crystallization ability of semi-aromatic nylon, characterized in that: It includes the following steps: The modified semi-aromatic nylon is prepared by mixing the semi-aromatic nylon with an alkaline solution and subjecting the mixture to heat treatment; The mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is ≥ 0.005:1; The alkali in the alkaline solution includes hypophosphite, phosphite, phosphate or alkali metal salt; The temperature of the heat treatment is greater than 60°C.
2. The method for improving the crystallization ability of semi-aromatic nylon according to claim 1, characterized in that: The method for improving the crystallization ability of semi-aromatic nylon satisfies one or more of the following conditions: (1) The structural formula of the semi-aromatic nylon is: Wherein a and n are positive integers, and Y is a C6-C8 phenyl group, for example (2) The relative viscosity of the semi-aromatic nylon is 2.0-3.0, for example, 2.24 or 2.61; (3) The number average molecular weight of the semi-aromatic nylon is 10000-500000, for example 32701 or 21094; (4) The weight average molecular weight of the semi-aromatic nylon is 10,000-500,000, for example, 74,259 or 48,968; (5) The preparation method of the semi-aromatic nylon comprises the following steps: In the presence of a catalyst, a dibasic acid, a diamine and a solvent are mixed to form a solution, and a polymerization reaction is performed to obtain the semi-aromatic nylon; and (6) The mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is (0.005-0.1):1, for example (0.005-0.05):1, for example (0.005-0.03):1, for example 0.005:1, 0.03:1 or 0.1:1; Preferably, the mass ratio of the alkali in the alkaline solution to the mass of the semi-aromatic nylon is (0.005-0.05):1, the alkali in the alkaline solution includes hypophosphite, phosphite, phosphate or alkali metal salt, and the temperature of the heat treatment is 80-150°C; Preferably, the mass ratio of the alkali in the alkaline solution to the mass of the semi-aromatic nylon is (0.005-0.05):1, the alkali in the alkaline solution is sodium hypophosphite, and the temperature of the heat treatment is 80-150° C., preferably 100-150° C.; Preferably, the mass ratio of the alkali in the alkaline solution to the semi-aromatic nylon is 0.03:1, the alkali in the alkaline solution is sodium acetate, potassium phosphite, magnesium phosphate or sodium formate, and the temperature of the heat treatment is 100°C.
3. The method for improving the crystallization ability of semi-aromatic nylon according to claim 2, characterized in that: The method for improving the crystallization ability of semi-aromatic nylon satisfies one or more of the following conditions: (7) a is a positive integer from 2 to 11, such as 4 or 8; The Y is (8) The catalyst is selected from at least one of phosphoric acid, hypophosphorous acid, phosphorous acid, phosphates, hypophosphites, phosphites, phosphites, and phosphates; (9) Based on the total weight of the dibasic acid, the diamine and the catalyst, the amount of the catalyst added is 0.01-0.2 wt%, for example 0.03 wt%; (10) The diamine is selected from one or more of p-phenylenediamine, m-phenylenediamine, p-phenylenediamine and m-phenylenediamine, preferably m-phenylenediamine; (11) The dibasic acid is selected from aliphatic diacids having 4 to 13 carbon atoms, such as aliphatic diacids having 6 or 10 carbon atoms, such as succinic acid, adipic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, preferably adipic acid and sebacic acid; (12) the molar ratio of the dibasic acid to the diamine is (0.96-1.05):1, preferably (0.98-1.03):1, for example 1.02:1; and (13) The polymerization reaction process includes a positive pressure reaction process, a normal pressure reaction process, and a negative pressure reaction process in sequence; During the positive pressure reaction, the pressure may be maintained at 400-800 kPa, for example 600 kPa; During the positive pressure reaction, the holding time may be 0.5-2 h, for example 1.5 h; During the normal pressure reaction, the holding time may be 20-60 min, for example 25 min; During the negative pressure reaction, the vacuum degree may be -100 to -20 kPa, for example -80 kPa; During the negative pressure reaction, the reaction time may be 10-100 min, such as 30 min or 60 min.
4. The method for improving the crystallization ability of semi-aromatic nylon according to claim 1, characterized in that: The method for improving the crystallization ability of semi-aromatic nylon satisfies one or more of the following conditions: (14) The hypophosphite includes an alkali metal hypophosphite or an alkaline earth metal hypophosphite; the alkali metal hypophosphite may be potassium hypophosphite and / or sodium hypophosphite, and the alkaline earth metal hypophosphite may be magnesium hypophosphite; (15) The phosphite includes an alkali metal phosphite or an alkaline earth metal phosphite; the alkali metal phosphite may be potassium phosphite and / or sodium phosphite, and the alkaline earth metal phosphite may be calcium phosphite; (16) The phosphate includes an alkali metal phosphate or an alkaline earth metal phosphate; the alkali metal phosphate may be potassium phosphate and / or sodium phosphate, and the alkaline earth metal phosphate may be calcium phosphate and / or magnesium phosphate; and (17) The alkali metal salt is a sodium salt and / or a potassium salt, such as potassium hypophosphite, sodium hypophosphite, potassium phosphite, sodium phosphite, potassium phosphate, sodium phosphate, sodium salt of C1-C5 fatty acids, potassium salt of C1-C5 fatty acids; the C1-C5 fatty acids may be C1-C4 fatty acids, such as formic acid, acetic acid, propionic acid, butyric acid; Preferably, the alkali in the alkaline solution is selected from one or more of hypophosphites, phosphites, phosphates and alkali metal salts; Preferably, the alkali in the alkaline solution is selected from one or more of the following combinations: potassium hypophosphite, sodium hypophosphite, magnesium hypophosphite, potassium phosphite, sodium phosphite, calcium phosphite, potassium phosphate, sodium phosphate, calcium phosphate, magnesium phosphate, sodium formate, potassium formate, sodium acetate, potassium acetate, sodium propionate, potassium propionate, sodium butyrate and potassium butyrate; Preferably, the alkali in the alkaline solution is selected from one or more of sodium hypophosphite, sodium acetate, potassium phosphite, magnesium phosphate and sodium formate, such as sodium hypophosphite, sodium acetate, potassium phosphite, magnesium phosphate or sodium formate.
5. The method for improving the crystallization ability of semi-aromatic nylon according to claim 1, characterized in that: The method for improving the crystallization ability of semi-aromatic nylon satisfies one or more of the following conditions: (18) The heat treatment temperature is 80 to 150°C, preferably 90 to 150°C, for example 100 to 150°C, and for example 80°C, 100°C, 120°C or 150°C; (19) The heat treatment time is 1 to 100 hours, for example 2 to 90 hours, for example 2 hours, 24 hours, 60 hours or 90 hours; (20) The heat treatment process is carried out under normal pressure or under positive pressure; (21) The ratio of the mass g of the semi-aromatic nylon to the volume mL of the alkaline solution is 1:1 to 1:10 g / mL, for example 1:2 g / mL; (22) The solvent in the alkaline solution is water; (23) The mass concentration of the alkali in the alkaline solution is 0.1 to 10 wt %, for example 0.5 to 5 wt %, for example 3 wt %.
6. The method for improving the crystallization ability of semi-aromatic nylon according to claim 1, characterized in that: The method for improving the crystallization ability of semi-aromatic nylon satisfies one or more of the following conditions: (24) The crystallization temperature of the modified semi-aromatic nylon is higher than the crystallization temperature of the semi-aromatic nylon, for example, the difference between the crystallization temperatures of the modified semi-aromatic nylon and the semi-aromatic nylon is ≥ 0.3°C, for example 0.4 to 4.5°C, for example 0.49°C, 0.76°C, 1.33°C, 1.35°C, 1.69°C, 1.87°C, 1.92°C, 1.95°C, 2.63°C, 2.81°C, 2.92°C, 3.98°C or 4.03°C; (25) The cold crystallization enthalpy of the modified semi-aromatic nylon is lower than the cold crystallization enthalpy of the semi-aromatic nylon; for example, the difference between the cold crystallization enthalpy ΔHc (J / g) of the modified semi-aromatic nylon and the semi-aromatic nylon is ≤-2.0 J / g, and another example is -2.0 to -15.0 J / g, and another example is -2.03 J / g, -2.85 J / g, -2.86 J / g, -4.02 J / g, -4.32 J / g, -4.67 J / g, -5.06 J / g, -5.27 J / g, -6.38 J / g, -6.7 J / g, -7.16 J / g, -8.5 J / g, -9.18 J / g, -10.4 J / g or -11.29 J / g.
7. A method for improving the crystallization ability of semi-aromatic nylon, characterized in that: It includes the following steps: The modified semi-aromatic nylon is prepared by mixing the semi-aromatic nylon with an alkaline solution and subjecting the mixture to heat treatment; The crystallization temperature of the modified semi-aromatic nylon is higher than the crystallization temperature of the semi-aromatic nylon, and the difference in crystallization temperature between the modified semi-aromatic nylon and the semi-aromatic nylon is ≥0.3°C; and / or the cold crystallization enthalpy of the modified semi-aromatic nylon is lower than the cold crystallization enthalpy of the semi-aromatic nylon, and the difference in cold crystallization enthalpy ΔHc (J / g) between the modified semi-aromatic nylon and the semi-aromatic nylon is ≤-2.0J / g.
8. A modified semi-aromatic nylon, characterized in that: The semi-aromatic nylon is prepared by the method for improving the crystallization ability of semi-aromatic nylon as described in any one of claims 1 to 7.
9. A poly(m-xylylene adipamide), characterized in that: The crystallization temperature of the poly(meta-xylylene adipamide) is greater than 159.22° C., and the cold crystallization enthalpy ΔHc (J / g) of the poly(meta-xylylene adipamide) is less than 19.59 J / g; Wherein, the crystallization temperature of the poly(m-xylylene adipamide) may be 159.4-163.5°C, such as 159.47°C, 159.74°C, 160.31°C, 160.33°C, 160.67°C, 160.85°C, 160.9°C, 160.93°C, 161.61°C, 161.79°C, 161.9°C, 162.96°C or 163.01°C; Wherein, the cold crystallization enthalpy ΔHc of the poly(m-xylylene adipamide) may be 8.0 to 19.0 J / g, for example, 8.9 J / g, 9.79 J / g, 11.01 J / g, 11.69 J / g, 13.03 J / g, 13.49 J / g, 13.81 J / g, 14.92 J / g, 15.13 J / g, 15.52 J / g, 15.87 J / g, 16.17 J / g, 17.33 J / g or 18.16 J / g.
10. A poly(m-xylylene sebacate), characterized in that: The cold crystallization enthalpy ΔHc (J / g) of the poly(m-xylylene sebacate) is less than 12.74 J / g, for example, 9.89 J / g.
Citation Information
Patent Citations
High-temperature-resistant semi-aromatic nylon nanocomposite and its preparation method
CN103804900A
Preparation method for polyamide 6 powdery material used for laser sintering
CN106905693A
Preparation method of anti-aging semi-aromatic nylon resin
CN107446129A
Polyamide composition as well as preparation method and application thereof
CN117777713A
Semi-aromatic polyamide resin composition and molded article obtained by molding the same
JP2020033548A